2018
DOI: 10.1007/s00247-018-4096-x
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of symptomatic upper-extremity venous thrombosis with multiple peripherally inserted central catheter insertions in pediatric patients

Abstract: Repetitive PICC insertions in the same arm are associated with an increased risk of symptomatic thrombosis. Double-lumen PICCs are associated with a higher risk of thrombosis compared to single-lumen lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Another possibility is a change in blood flow at the tip or the difference in the stiffness of the catheter. 53 It is generally believed that there is a positive correlation between CRT formation and CLABSI. 54 We found that CLABSI can increase the risk of CRT.…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility is a change in blood flow at the tip or the difference in the stiffness of the catheter. 53 It is generally believed that there is a positive correlation between CRT formation and CLABSI. 54 We found that CLABSI can increase the risk of CRT.…”
Section: Discussionmentioning
confidence: 99%
“…108 Color Doppler is useful technique to detect the vessel and thrombosis. 105,106,109 • Thrombosis (thrombophlebitis): venous thrombosis could be caused from an inserted catheter and patient conditions such as an underlying disease, or inadequate prophylaxis (►Figs. 22 and 23).…”
Section: Timing Of Occurrence and Strategy Of Diagnosismentioning
confidence: 99%
“…However, arm veins should be avoided in patients with potential future need of hemodialysis (chronic kidney disease higher than grade G2A2 or G3a 85 ) because of the cumulative risk of thrombosis and loss of potential AV fistula sites. 26,86 For chronic intermittent access, an indwelling venous port may be placed in the veins of the chest, extremity, or groin. Ports should be used with caution in patients who are immunocompromised at the time of insertion.…”
Section: Elective Access Conditionsmentioning
confidence: 99%
“…Peripherally inserted central catheters are an acceptable alternative. However, arm veins should be avoided in patients with potential future need of hemodialysis (chronic kidney disease higher than grade G2A2 or G3a) because of the cumulative risk of thrombosis and loss of potential AV fistula sites . For chronic intermittent access, an indwelling venous port may be placed in the veins of the chest, extremity, or groin.…”
Section: Failure Points and Essential Components Of Carementioning
confidence: 99%